Investigation on interferon alpha-inducible protein 6 (IFI6) gene as a candidate for meat and carcass quality in pig - A. Kayan (2018)
The aim of this research was to screen for polymorphism and to perform an association study of IFI6 with meat and carcass quality traits. A SNP (g.370A>G) was detected which was associated (P< 0.05) with meat colour, pH 24. h post mortem (p.m.) in ham, conductivity 45. min. p.m. in loin and conductivity 24. h. p.m. in ham, drip loss and carcass length in Duroc × Pietrain and with meat colour, muscle area and ham percentage in the Pietrain population. Highest expression of IFI6 mRNA was detected in skeletal muscle (longissimus dorsi) by qRT-PCR comparing different tissues. Both qRT-PCR and western blot revealed that the IFI6 gene and protein expressions were significantly (P< 0.05) higher in skeletal muscle with low drip loss compared to that of high drip loss. IFI6 protein was localized in the myocytes membrane. Results suggested that IFI6 might play roles in meat and carcass quality and is a potential positional, physiological and functional candidate gene for improving meat quality traits in pigs. © 2011 Elsevier Ltd.